Complexity science and theory development for the futures field - Samet, Robert H. (Futures : the journal of policy, planning and futures studies, 2012)
► Complexity science unifies some forty diverse features applicable to the futures field. ► Macrolaws may be formulated for civil and social emergence. ► Civil or societal phase transitions are driven by investment capital. ► Critical intervention points in the global macrosystems can result in a beneficial change to the system. ► A resilient macrostructure can evolve to absorb extreme events. Complexity science unifies some forty diverse features that arise from the evolution of the civil system and these underlie theory development in the futures field. The main features of an evolutionary methodology deal with emergence, macrolaws, civil or societal transitions, macrosystem design, and the absorption of extreme events. The following principles apply: (1) The civil system is an open system in which investment capital is the system growth parameter that drives it away from equilibrium, with the formation of spatial structure. (2) The historical circumstances of human settlements provide a path dependency in respect of natural resources, defence, energy, transport, or communications. (3) Emergent properties arise within a complex adaptive system from which a theory of the system can be formulated, and these are not deducible from the features of the transacting entities. (4) Futures research identifies the conditions that will lead to an irreversible civil or societal phase transition to a new stage of development. (5) Emergent behaviour in the macrostructure at regional or continental levels can be influenced through critical intervention points in the global macrosystems.